Serial Winning Coaches: People, Vision, and Environment - Mallett, C. J.; Lara-Bercial, S. (2016)
To enhance our understanding of the practices of successful people, a more comprehensive and nuanced examination of what underpins their successes is imperative; that is, why they behave the way they do. In this chapter, we provide an insight into what we have learned about highly successful elite sport coaches and how this understanding might inform coach recruitment and development. A "logic of person perception" approach to data analysis was used to make sense of the multiple data sets (surveys, interviews) representing multiple layers of a person`s psychology. In this research, 14 serial winning coaches (SWC) from 11 countries and 10 sports (128 medals) contributed multiple data sets that were complemented with data from some of their successful athletes. Overall, these SWC were high on conscientiousness and extraversion and low on neuroticism. Their striving content showed they were agentic and approach-oriented. Moreover, their dominant motivational themes were learning and personal growth, achievement, and power. Three key themes emerged from the interview data: vision, people, and environment. A metastory of these SWC portrays them as righteous adventurers with a higher purpose, and as a grounded realist. We conclude with several recommendations for coach developers on the basis of this research.